Gene capture from across the grass family in the allohexaploid Elymus repens (L.) Gould (Poaceae, Triticeae) as evidenced by ITS, GBSSI, and molecular cytogenetics - Mahelka, Václav; Kopecký, David (Molecular biology and evolution, 2010)
Four accessions of hexaploid Elymus repens from its native Central European distribution area were analyzed using sequencing of multicopy (internal transcribed spacer, ITS) and single-copy (granule-bound starch synthase I, GBSSI) DNA in concert with genomic and fluorescent in situ hybridization (GISH and FISH) to disentangle its allopolyploid origin. Despite extensive ITS homogenization, nrDNA in E. repens allowed us to identify at least four distinct lineages. Apart from Pseudoroegneria and Hordeum, representing the major genome constituents, the presence of further unexpected alien genetic material, originating from species outside the Triticeae and close to Panicum (Paniceae) and Bromus (Bromeae), was revealed. GBSSI sequences provided information complementary to the ITS. Apart from Pseudoroegneria and Hordeum, two additional gene variants from within the Triticeae were discovered: One was Taeniatherum-like, but the other did not have a close relationship with any of the diploids sampled. GISH results were largely congruent with the sequence-based markers. GISH clearly confirmed Pseudoroegneria and Hordeum as major genome constituents and further showed the presence of a small chromosome segment corresponding to Panicum. It resided in the Hordeum subgenome and probably represents an old acquisition of a Hordeum progenitor. Spotty hybridization signals across all chromosomes after GISH with Taeniatherum and Bromus probes suggested that gene acquisition from these species is more likely due to common ancestry of the grasses or early introgression than to recent hybridization or allopolyploid origin of E. repens. Physical mapping of rDNA loci using FISH revealed that all rDNA loci except one minor were located on Pseudoroegneria-derived chromosomes, which suggests the loss of all Hordeum-derived loci but one. Because homogenization mechanisms seem to operate effectively among Pseudoroegneria-like copies in this species, incomplete ITS homogenization in our samples is probably due to an interstitial position of an individual minor rDNA locus located within the Hordeum-derived subgenome.
Keywords: lipnicovité; DNA, Intergenic; Cytogenetic Analysis; rostlinné geny; fylogeneze; DNA, Ribosomal; Genes, Plant; ribozomální DNA; cytogenetické vyšetření; hybridizace in situ fluorescenční; Gene Transfer, Horizontal; Bayesova věta; genetická transkripce; Databases, Genetic; modely genetické; pseudogeny; intergenová DNA; databáze genetické; Bayes Theorem; Poaceae; Starch Synthase; přenos genů horizontální; Models, Genetic; Phylogeny; Transcription, Genetic; Pseudogenes; synthasa škrobu; In Situ Hybridization, Fluorescence